Structure and Properties of One‐dimensional Homometallic Complexes [Cu5(CN)5(5‐ph‐2, 2′‐bpy)3]n and [Cu(SCN)(5‐ph‐2, 2′‐bpy)]n (5‐ph‐2, 2′‐bpy = 5‐Phenyl‐2, 2′‐bipyridine)1. Issue 8 (27th May 2015) - Cui, Shuxin; Zuo, Minghui; Wang, Haiyu; Xu, Jie
Abstract: The complexes [Cu5 (CN)5 (5‐ph‐2, 2′‐bpy)3 ] n (1 ) and {Cu(SCN)(5‐ph‐2, 2′‐bpy)} n (2 ) were prepared by reaction of CuCl2 with different bridging ligands such as cyanide‐ or thiocyanate under hydrothermal conditions in the presence of 5‐phenyl‐2, 2′‐bipyridine (5‐ph‐2, 2′‐bpy). The copper ions are bridged by cyanide anions to form 1D ribbon with 26‐membered {Cu10 (CN)8 } rings in complex1, whereas the metal ions are bridged by thiocyanate anions to form a 1D chain in complex2 . Abstract :